2003
DOI: 10.1111/j.1346-8138.2003.tb00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Chondrolipoma: Possible Importance of Transforming Growth Factor (TGF) ‐βs, Latent TGF‐ β Binding Protein‐1 (LTBP‐1), and Bone Morphogenetic Protein (BMP) for Chondrogenesis in Lipoma

Abstract: To clarify the pathogenesis of chondrolipoma, we examined the expressions and localizations of TGF-beta1, -beta2, -beta3, BMP, and LTBP-1 in our rare case by immunohistochemical staining, and compared them with the staining patterns seen in normal human tracheal cartilage tissue and osteochondroma (controls). In the present case, there was weak TGF-beta1 expression in both lacuna and spindle cells around the cartilage, intense TGF-beta2 expression in both lacuna and spindle cells, and weak-to-moderate TGF-beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Chondrolipoma is a rare form of benign mesenchymoma containing mature cartilage and adipose tissue 1,2 . A limited number of chondrolipomas have been reported in the English language published work 1,2 and also in Japanese 3–12 . Herein, the author describes an early chondrolipoma of the popliteal fossa with review of the Japanese published work.…”
Section: Introductionmentioning
confidence: 99%
“…Chondrolipoma is a rare form of benign mesenchymoma containing mature cartilage and adipose tissue 1,2 . A limited number of chondrolipomas have been reported in the English language published work 1,2 and also in Japanese 3–12 . Herein, the author describes an early chondrolipoma of the popliteal fossa with review of the Japanese published work.…”
Section: Introductionmentioning
confidence: 99%
“…The second is that the cartilage may originate from multipotential cells in the mesenchymoma. A previous immunohistochemical study supported the explanation that the pattern of expression for growth factor-β, latent transforming growth factor-β binding protein-1 transforming, and bone morphogenetic protein might play an important role in the transformation of multipotential cells into the chondrolipoma (11). Considering the proximity of the identified chondrolipoma to the iliac bone of our case study, we agree with the first explanation of chondroid-osseous metaplasia, which states that the mass may be a result of a micro-trauma.…”
Section: Discussionmentioning
confidence: 82%
“…Mechanical trauma and frequent contact with periosteum, tendons or joint capsules might increase the possibility of this metaplasia 3 . Immunohistochemical study concluded that chondrogenesis in lipoma may be enhanced by overproduction of transforming growth factor (TGF bs) and bone morphogenetic protein (BMP) 7 . Chondrolipoma is mainly encountered in large-sized, long-standing lipomas and most of these tumours are solitary and circumscribed.…”
Section: Discussionmentioning
confidence: 99%